2009
DOI: 10.1128/jvi.00715-09
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Nonstructural Proteins Decrease Levels of Multiple Members of the Cellular Interferon Pathways

Abstract: Viruses of the Paramyxoviridae family, such as the respiratory syncytial virus (RSV), suppress cellular innate immunity represented by type I interferon (IFN) for optimal growth in their hosts. The two unique nonstructural (NS) proteins, NS1 and NS2, of RSV suppress IFN synthesis, as well as IFN function, but their exact targets are still uncharacterized. Here, we investigate if either or both of the NS proteins affect the steady-state levels of key members of the IFN pathway. We found that both NS1 and NS2 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
160
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(166 citation statements)
references
References 76 publications
3
160
2
1
Order By: Relevance
“…In this line, we unveil for the first time that DUOX2 is critical for the outcome of respiratory virus infections through its key function in the establishment of the antiviral state specifically induced by the synergistic action of IFNβ and TNFα secreted during SeV infection. The capacity of RSV to counteract this novel antiviral pathway adds to its previously recognized capacity to interfere with other key antiviral events, including RIG-I-dependent signaling or IKKε, TRAF3 or STAT2 stability [33,34]. Altogether, these evasion mechanisms contribute to the development of RSV-associated diseases.…”
Section: Rsv Interferes With the Expression Of Duox2mentioning
confidence: 99%
“…In this line, we unveil for the first time that DUOX2 is critical for the outcome of respiratory virus infections through its key function in the establishment of the antiviral state specifically induced by the synergistic action of IFNβ and TNFα secreted during SeV infection. The capacity of RSV to counteract this novel antiviral pathway adds to its previously recognized capacity to interfere with other key antiviral events, including RIG-I-dependent signaling or IKKε, TRAF3 or STAT2 stability [33,34]. Altogether, these evasion mechanisms contribute to the development of RSV-associated diseases.…”
Section: Rsv Interferes With the Expression Of Duox2mentioning
confidence: 99%
“…These results also reveal that although NS1 and NS2 display some preferences, there is a significant degree of overlap in their targets. The inhibitory activity is nonetheless specific, as the expression levels of MAVS, LGP2, STAT1, TRIF, MyD88 and numerous IFN signaling-unrelated cellular proteins that we have tested, such as L13a ( Figure 1A), actin [28], GAPDH and SP6 (data not shown), were not affected by the ectopic expression of NS1 and/or NS2. We proposed that this is indicative of the ability of NS proteins to form specific degradative complex(s), which we set out to study.…”
Section: An Expanding List Of Cellular Innate Immune Proteins Targetementioning
confidence: 99%
“…We and others [16][17][18][19][20][21][22][23][24][25][26][27][28][29] have recently shown that NS1 and NS2 inhibit and/or degrade a number of proteins of the IFN induction and response pathways. We have since screened other members of these pathways, confirmed and extended the repertoire of NS targets to include: RIG-I, TRAF3, IKKε, IRF3, IRF7 and STAT2 ( Figure 1A).…”
Section: An Expanding List Of Cellular Innate Immune Proteins Targetementioning
confidence: 99%
See 2 more Smart Citations